Estudo de conceitos de termologia usando um aquecedor solar de baixo custo - Coletto, Emerson Rodrigo (2020)
Teaching Physics in High School, specifically in public schools, is a major challenge today. To overcome it, it is essential to adopt innovative teaching practices and, in this sense, this study proposes to teach concepts of Thermology using a low cost automated solar heater. The heater sensors were coupled to an Arduino platform to control the process. In this proposal, DS18B20 temperature sensors were used, which are waterproof and measured the values on the surface, in the middle and bottom of the reservoir, in addition to a fourth sensor installed in the collector. The obtained data can be accessed next to the Micro SD Recorder Module, which is a component connected to the Arduino. The temperature values were analyzed in the classroom and served as facilitators of a meaningful learning of some concepts of Physics such as: temperature, heat, thermometric scales, thermometers, amount of heat, sensitive heat, latent heat, thermal conductivity and solar radiation. It has also been proposed to use the alternative solar heater in the context of domestic energy savings. With this work, it was possible to have greater dynamics in Physics classes, making them more attractive and playful, resulting in motivation on the part of students at all stages of learning.